Characterizing Opine Physiological and Genetic Diversity in Moroccan strains of Allorhizobium vitis, the Causal Agent of Grapevine Crown Gall - Khaoula Habbadi; Hajar Hamzaoui; Imane Hourmatallah; Hiba Yahyaoui; Faiçal Aoujil; Majida Hafidi; Aziz Aziz; Salma El Iraqui El Houssaini (African and Mediterranean Agricultural Journal - Al Awamia)
This study investigates the physiological and genetic diversity of Allorhizobium vitis strains in Morocco, focusing on their ability to produce and utilize opines as sources of carbon, nitrogen, and energy. Using ultra-high performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF) and specific PCR assays, we identified and characterized opines in tumors induced in tomato plants by Moroccan strains of A. vitis. All strains showed the rare octopine/vitopine combination. Chromatographic analysis and molecular validation revealed metabolic and genetic uniformity in opine catabolism among the strains. These results suggest a homogeneity of octopine/vitopine tumour-inducing plasmids (pTi), which contribute to the uniformity of opine-related genes. This comprehensive approach provides insights into the molecular mechanisms of opine utilization and bacterial virulence, suggesting that targeting specific pathways or key virulence genes may be a strategy to control crown gall disease.